Rethinking Economics: Embracing Sustainability and Human Well-Being - Ka Wing Mo (Köz-gazdaság)
Taking an insightful and thought-provoking look at alternative economic systems, the book "The New Economics: A Bigger Picture", published by David Boyle and Andrew Simms, is highly recommended. The writers question the traditional way of thinking about economics. Instead, they would champion a system that puts a lot more emphasis on the well-being of humans and the sustainability of the environment than it does merely on profit. I find this book very exceptional and enjoyable to read because it helps me understand the problems with the standard or traditional economics and the chance for a more fair and long-lasting future.